FMCW-Radarsignalverarbeitung zur Entfernungsmessung mit hoher Genauigkeit - Scherr, Steffen (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2017)
Distance measurements with micrometer accuracies are essential for the control of industrial machines. This work investigates the maximum possible accuracy of FMCW radar systems, which use an additional phase evaluation. The feasibility of the developed techniques is shown in different industrial applications. An accuracy better than 1 µm is demonstrated in measurements.